Market Power and Duration of R&D Investment in a Panel of Italian Firms - Maria Elena Bontempi; Luca Lambertini; Erica Medeossi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
Studies about innovation find evidence of a positive relationship between technological advancement and firm performance, in particular when the innovative effort is continuous. This paper aims to further the analysis on the duration of R&D investment at the firm level. The contribution of this study is threefold: first, we extend Má\~nez et al. [2014], Triguero et al. [2014] analysis for Spain to the Italian case: we use a panel of manufacturing and service companies, thus enlarging the view of R&D duration within the European countries. Secondly, from a methodological point of view, we employ both discrete- and continuous-time duration models, in order to test the Proportional Hazards (PH) assumption, i.e. the assumption that the hazard rate is equivalent over time across groups. Last, but not least, we assess whether a firm's likelihood of continuing investment in R&D depends on the market power of companies. We test alternative measures for market power: the classical price-cost margin and a new proxy for the firm demand elasticity, obtained from a specific survey question. Results are in line with the hypothesis that R&D presents considerable temporal spill overs and strong persistence, even once unobserved heterogeneity is controlled for. Also, we argue that the appropriate proxy for market power is the firm demand elasticity, and we find support for the Schumpeterian hypothesis.
Keywords: C23; C41; D22; G32; L10; O30; 330